Study of UGT1A1*28 genetic polymorphism related to irinotecan response in Kinh Vietnamese - Hai Ha, Nguyen; Thi Thanh Hoa, Nguyen; Binh Giang, Vu; Phuong Nhung, Vu; Thi Thu Yen, Hoang; Dang Ton, Nguyen; Thi Nhu Quynh, Bach (Vietnam Journal of Biotechnology, 2020)
Irinotecan is a medicine commonly used to treat cancer. Carboxylesterase converts irinotecan into SN-38, a substance with 100 times more cytotoxicity than the original compound. SN-38 is inactivated by glucuronidation in the liver to the inactive form of SN-38 glucuronidation. UGT1A1 is the main enzyme responsible for the glucuronidation SN-38 secretion. Neutropenia and diarrhea are dose-limiting toxicity of the drug. UG1A1*28 variant is believed to increase the risk of neutropenia and is closely related to the risk of severe diarrhea. In this study, we used the direct sequencing method of the promoter UGT1A1 gene to determine the genotype and allele frequency of UGT1A1*28 in 95 individuals of healthy Kinh Vietnamese . The results showed that UGT1A1*28 variant is present in homozygousand heterozygous genotypes with frequencies of 14.74% and 1.05%, respectively. The allele frequency of the UGT1A1*28 variant was 8.421% which was small compared with the wild type allele *1 (91.579%). The data obtained from the study contribute to an effective cancer treatment solution using the drug irinotecan.